Chemotherapeutic hormesis induced by the tumor microenvironment in refractory ovarian cancer - Xuboya Chang; Satoshi Tamauchi; Atsushi Nakagawa; Wang Xinyuan; Kosuke Yoshida; Akira Yokoi; Nobuhisa Yoshikawa; Hiroaki Kajiyama (Scientific Reports)
Abstract Advanced ovarian cancer often presents with multiple lesions exhibiting varying responses to chemotherapy, highlighting the critical influence of the tumor microenvironment (TME). This study investigates the phenomenon of chemotherapeutic hormesis, wherein low doses of chemotherapeutic agents, such as cisplatin (CDDP) and paclitaxel (PTX), paradoxically stimulate rather than inhibit cancer cell proliferation. Our findings indicate that NOS3 ovarian cancer cells, particularly drug-resistant variants, exhibit enhanced proliferation when exposed to low concentrations of these drugs. This effect is further amplified under hypoxic conditions, suggesting that the TME plays a pivotal role in modulating chemotherapeutic outcomes. Mechanistically, low-dose CDDP upregulates pathways involved in cell cycle progression, specifically the G2/M checkpoint and mitotic spindle formation, accelerating rather than arresting the cell cycle. Furthermore, the activation of the reactive oxygen species (ROS) pathway and increased glutathione levels indicate increased cellular response to oxidative stress, further contributing to cell survival and proliferation. These findings challenge traditional treatment strategies that prioritize the maximization of drug dosage, suggesting that a more nuanced approach considering the influence of the TME and the potential for hormesis could improve therapeutic outcomes. Understanding the mechanisms driving chemotherapeutic hormesis is essential for developing more effective treatments for refractory ovarian cancer. Future research should focus on mitigating the impact of hormesis to enhance the efficacy of chemotherapy in resistant cancer types.